A review of the current literature and a guide to the early diagnosis of autoimmune disorders associated with neuromyelitis optica. (May 2014) - Iyer, Anand; Elsone, Liene; Appleton, Richard; Jacob, Anu
Abstract Neuromyelitis optica (NMO) is an immune-mediated neurological disorder characterised by recurrent episodes of optic neuritis and longitudinally extensive transverse myelitis. A serum biomarker, aquaporin-4 IgG, the autoantibody against aquaporin-4 water channel, has been specifically associated with NMO and has assisted early recognition and prediction of relapses. Less commonly, a monophasic course, associated with antibodies to myelin oligodendrocyte glycoprotein has been reported. Specific diagnostic criteria have been defined; however, some cases that do not fulfil these criteria (but are nevertheless associated with aquaporin-4 IgG) are classified as NMO spectrum disorder and follow the same relapsing course. An ever-growing list of autoimmune disorders, both organ-specific and non-organ-specific, have been associated in up to 20–30% of patients with NMO. These disorders, which may become symptomatic before or after the development of NMO, are often diagnosed long after the diagnosis of NMO, as symptoms may be wrongly attributed to NMO, its residual effects or medication side effects. In addition, autoantibodies can be found in patients with NMO without coexisting disease (up to 40% in some series) and maybe suggestive of a heightened humoral immune response. We present a comprehensive review of the current literature on autoimmune disorders co-existing with NMO and identified 22 autoimmune conditions (myasthenia gravis, coeliac disease, ulcerative colitis, sclerosing cholangitis, systemic lupus erythematosus, rheumatoid arthritis, antiphospholipid antibody syndrome, Sjogren's syndrome, autoimmune hypothyroidism, immune thrombocytopenic purpura, pernicious anaemia, narcolepsy, pemphigus foliaceus, alopecia areata, psoriasis, scleroderma, dermatitis herpetiformis, polymyositis, chronic inflammatory demyelinating polyneuropathy, paraneoplastic disorders, insulin dependent diabetes mellitus and autoimmune encephalitis).